Respecting the GDPR in Online Interviewed Focus Groups - Goberna Caride, Carolina (Journal of Audiovisual Translation, 2021)
Since March 2020 the Corona virus has limited personal encounters due to social distancing measures. Thus, many data collection techniques relying on face-to-face interaction, like interviews or Focus Groups (FG), are now being practised in online environments. Such change requires the implementation of innovative measures to comply with Regulation EU 2016/679 (GDPR) and obey national data protection laws. Processing personal data of voluntary participants has to have a lawful ground and a clear purpose behind it. Moreover, the researcher has to respect legal requirements and principles for processing personal data, provide the participants with information about the research procedure and apply security measures to avoid risks to the rights and freedoms of individuals. This process has to apply to any interaction mediated by Web-Conferencing Systems (WCS). The purpose of this paper is to describe the legal requirements for conducting online interviews or FG under social distancing conditions. The project of reference for the application of these requirements is the EU Horizon2020 HELIOS project consisting of the development of a decentralised social media platform. Lay summary At universities or in industry researchers can interview people personally to test, for instance, the use of a specific technology. The objective is to collect data for future improvements. In 2020 people all over the world found themselves in a pandemic. The Covid-19 limited social meetings with beloved ones and also restricted the work of scientific researchers. Individual or group interviews could not take place in presence. Thus, a solution was seen in online conferencing platforms such as Zoom. Modifying the space and the way in which an interview takes place poses some legal challenges regarding data protection. Such conversations with individuals always have to apply European and national data protection laws. Among other things, this means that there needs to be a specific legal reason to process personal data and a specific purpose behind the interview. Additionally, the researcher has to inform participants about all the legal terms, legal guarantees and research procedure. All this applies as well if online conferencing platforms are used. In this article, you can find a description of the necessary legal steps to develop online interviews with individuals or focus groups and fulfil European data protection requirements.